2018
DOI: 10.1016/j.bja.2018.01.040
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine metabolic clearance is not affected by fat mass in obese patients

Abstract: NCT02557867.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In addition, they also showed that for any lean body mass, total CL decreased associated with major fat mass. In a second trial by the same study group, authors confirmed that lean body mass was an appropriate dosing scalar for size in obese patients and showed that decreased hepatic blood had a significant effect on the CL of DEX (Rolle et al, 2018). The observed CL reduction in this population is most probably explained by a relative overdose of obese patients caused by TBW-based dosing schemes.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, they also showed that for any lean body mass, total CL decreased associated with major fat mass. In a second trial by the same study group, authors confirmed that lean body mass was an appropriate dosing scalar for size in obese patients and showed that decreased hepatic blood had a significant effect on the CL of DEX (Rolle et al, 2018). The observed CL reduction in this population is most probably explained by a relative overdose of obese patients caused by TBW-based dosing schemes.…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 86%
“…The observed CL reduction in this population is most probably explained by a relative overdose of obese patients caused by TBW-based dosing schemes. In this setting, scaling doses to FFM or allometric TBW seems more relevant (Cortinez et al, 2015;Hannivoort et al, 2015;Rolle et al, 2018).…”
Section: Pharmacokinetic Propertiesmentioning
confidence: 99%
“…The liveralong with the kidney-plays a central role in the clearance of peripheral circulating amyloid beta through metabolic detoxification. In the state of hepatic inflammation and especially in more advanced stages like cirrhosis, amyloid beta uptake into hepatocytes and consequently excretion into the bile may be impaired leading to higher amyloid beta levels in the circulation [22,[24][25][26]. A recent genetic analysis performing network clustering analyses found 189 shared genes between NAFLD and Alzheimer's disease and illustrated shared pathways between both diseases including long fatty acid metabolism, IL-17 signaling, and carbohydrate metabolism [27].…”
Section: Discussionmentioning
confidence: 99%
“…In this model, all structural parameters were allometrically scaled using a fixed exponent of 0.75 on clearance parameters (CL, Q) and 1 on volumes of distribution (V 1 , V 2 ) (Eqs. [1][2][3][4]. A sigmoidal function was used to describe maturation of clearance, including a maturation half-life (TM 50 ) which represents the postmenstrual age (PMA) at which maturation has reached 50% of the adult value, and an exponent (Hill factor, N) describing the steepness of the maturation curve (Eq.…”
Section: Initial Dose Selectionmentioning
confidence: 99%
“…It is metabolised by glucuronidation and CYP2A6 hydroxylation and subsequently excreted in urine almost exclusively as metabolite [2]. Its pharmacokinetics has been described by a two-compartmental model both in adults [3][4][5][6][7] and children [8][9][10][11][12]. Still, other investigators have also reported the disposition of dexmedetomidine according to one-compartment [13] and three-compartment [14][15][16] models.…”
Section: Introductionmentioning
confidence: 99%